The Impact of Talent Management on Organizational Health: An Applied Study on Workers in the Emirate of Jazan Region - Ghazwani, Ahmed Hassan; Alariki, Baseim Qaid (Journal of Economic, Administrative and Legal Sciences, 2025)
The aim of the research was to identify the impact of talent management on organizational health. This is an applied study on employees in the Emirate of Jazan Region. The study population represents all employees in the Emirate of Jazan Region, numbering 500 employees. The study tool was a questionnaire that was applied to a sample of (192 employees). The research reached several results, the most important of which are: There is a positive statistically significant impact at the significance level (0.000) of talent management in its four dimensions (talent attraction, talent development, talent compensation, talent retention) on organizational health. The magnitude of the impact of talent attraction on organizational health reached 0.484, the magnitude of the impact of talent development on organizational health reached 0.462, the magnitude of the impact of talent compensation on organizational health reached 0.49, and the magnitude of the impact of talent retention on organizational health reached 0.533. The research also found that there are no statistically significant differences between the research sample items regarding the impact of talent management on organizational health in the Emirate of Jazan Region, which are due to demographic characteristics (gender, age, and Length of service and educational qualifications. The results also indicated that the level of talent management was high, with an arithmetic mean of 4.02, representing 80.41% of the total respondents, and a "yes" rating. The organizational health axis also received a high rating, with an arithmetic mean of 4.109, representing 82.18% of the total respondents, and a "yes" rating. Based on the research results, the researchers recommend that the Emirate of Jazan Region establish a dedicated talent management department in the Emirate of Jazan Region, focused on discovering, attracting, developing, compensating, and retaining talent.
Keywords: Talent Management; Talent Attraction; Talent Development; Compensation; Talent Retention; Organizational Health